KECEPATAN PERGERAKAN MAGMA DASIT KE PERMUKAAN DI DAERAH PURWOREJO DAN SEKITARNYA, JAWA TENGAH Berdasarkan Analisis Penarikhan Jejak Belah - Sam Permanadewi; I. Saefudin; D. A.Siregar (Jurnal Geologi dan Sumberdaya Mineral, 2008)
Zircon fission track dating using zirkon of four dacite samples from Purworejo, yielded age of 12,6 ± 1,5 to 15,9 ± 1,0 m.a. One cooling phase of the dacite body at Purworejo area indicates an uplift velocity of 0.02 - 0.06 mm / year. Keywords : fission tracks, zircon, uplift, Purworejo